Evaluation of Visual and Subjective Outcomes with Mix-and-Match of Three One-Piece Tecnis Multifocal IOLs of Varying Add Powers - Dell SJ (Dove Medical Press, 2020)
Steven J Dell Dell Laser Consultants, Austin, TX, USACorrespondence: Steven J DellDell Laser Consultants, Austin, TX, USATel +1 512-347-0255Email steven@dellmd.comPurpose: To evaluate visual and subjective outcomes after bilateral mix-and-match implantation of one-piece diffractive multifocal IOLs in different near add powers (+2.75 D, +3.25 D, +4.0 D).Setting: Four US clinics.Design: Prospective, multi-center, parallel comparison clinical study design.Patients and Methods: Two treatment groups received implantation with either the +3.25 D (ZLB00) or the +4.00 D (ZMB00) Tecnis® Multifocal 1-piece IOL in their non-dominant eye, and the +2.75 D (ZKB00) Tecnis Multifocal 1-piece IOL in their dominant eye (Abbott Medical Optics, Inc., Santa Ana, CA). Each study patient underwent the same routine cataract extraction procedures for each eye, with the second eye scheduled to undergo cataract extraction within 7 to 30 days after the 1st eye surgery. Visual and subjective outcomes were evaluated at 90 days after 2nd eye surgery for the two groups: +3.25D/+2.75D (n=41) and +4.00D/+2.75D (n=36).Results: Mean binocular uncorrected distance visual acuities at 90 days postop were 0.02 ± 0.082 (+3.25D/+2.75D) vs 0.07 ± 0.128 (+4.00D/+2.75D) (p=0.025). Mean binocular uncorrected intermediate visual acuities at 90 days postop were 0.14 ± 0.185 (+3.25D/+2.75D) vs 0.26 ± 0.261 (+4.00D/+2.75D) (p=0.024). Mean binocular uncorrected near visual acuities at 90 days postop were 0.06 ± 0.098 (+3.25D/+2.75D) vs 0.19 ± 0.286 (+4.00D/+2.75D) (p=0.018). Over 88% of patients reported “none” for visual symptoms of glare, halos, starburst, or other. Freedom from glasses or contacts was reported by groups +3.25D/+2.75D and +4.00D/+2.75D as follows: distance (95.1% vs 97.1%), intermediate (92.7% vs 94.1%), and near activities (82.9% vs 64.7%).Conclusion: At 90 days postoperatively, both groups demonstrated good visual and subjective outcomes; however, differences in near and intermediate outcomes favored the +3.25/+2.75 IOL combination.Clinicaltrials.gov Registration: NCT02863159 (08/11/2016).Keywords: extended range of vision, TECNIS multifocal IOL, ZKB00, ZLB00, ZMB00, cataract, blended vision, contralateral, mix-and-match